2019
DOI: 10.1016/j.bjorl.2017.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Does the reduction of inferior turbinate affect lower airway functions?

Abstract: This study demonstrated that the widening of the nasal passage after the reduction of the inferior turbinate size had a favorable effect on the pulmonary function tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…15 Similarly Unsal conducted a study on the reduction of ITH and its effect on the nose volume and found that the total volume of nose increased significantly after the treatment of ITH (p<0.001). 13 This study is also in consistence with Kaymakci's result who reported that both frequency and severity of nasal obstruction were significantly reduced after the reduction of the size of the inferior turbinate with radiofrequency and lateral displacement (p<0.001). [16][17][18]…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…15 Similarly Unsal conducted a study on the reduction of ITH and its effect on the nose volume and found that the total volume of nose increased significantly after the treatment of ITH (p<0.001). 13 This study is also in consistence with Kaymakci's result who reported that both frequency and severity of nasal obstruction were significantly reduced after the reduction of the size of the inferior turbinate with radiofrequency and lateral displacement (p<0.001). [16][17][18]…”
Section: Discussionsupporting
confidence: 85%
“…12 Similarly in a Turkish study mean age of the patients was 32.16 ± 10.48 years (range 20-59 years). 13 The reason is that the 3 rd and 4 th decade is the most active time of life, one can be affected easily by environmental hazards and seeks asolution on apriority basis to eliminateany health issues.…”
Section: Discussionmentioning
confidence: 99%
“…Various procedures, such as the RF-assisted uvulopalatoplasty or RFassisted tongue base reduction have been described and are feasible under local anaesthesia, which is another important advantage of RF-surgery [8][9][10][11]. A further popular application is the tissue reduction of the inferior turbinates in the treatment of nasal obstruction due to nasal concha hyperplasia [12,13]. Despite the uptrend of RF-based procedures in head and neck surgery, there is no information on the characteristics of RFassisted resection of tumors of the oral cavity or the oropharynx available.…”
mentioning
confidence: 99%